2004
DOI: 10.1021/jp049575z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Study of the O + HO2 Reaction Using Two DMBE Potential Energy Surfaces:  The Role of Vibrational Excitation

Abstract: We investigate the effect of vibrational excitation on the dynamics and kinetics of the atmospheric reaction O( 3 P) + HO 2 f OH + O 2 using two double many-body expansion potential energy surfaces previously reported. The results show that such an effect is relatively minor even considering HO 2 with contents of vibrational excitation close to the H + O 2 dissociation asymptote. It should therefore not bear drastic implications in atmospheric modeling where such an effect has been ignored thus far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 49 publications
6
37
4
Order By: Relevance
“…Meanwhile, the OH bond remains almost as a spectator, keeping its ro-vibrational distribution as originally was in HO 2 . Similar results have been observed for the reaction O + HO 2 when O 2 is formed [22] with a high rotational temperature.…”
Section: Resultssupporting
confidence: 87%
“…Meanwhile, the OH bond remains almost as a spectator, keeping its ro-vibrational distribution as originally was in HO 2 . Similar results have been observed for the reaction O + HO 2 when O 2 is formed [22] with a high rotational temperature.…”
Section: Resultssupporting
confidence: 87%
“…As for the O + OH reaction, the strong correlation between the parameters suggests that their physical significance should be seen with caution. Also shown for comparison in Figure 10 are the results calculated for a vibrational energy of HO 2 equal to the ZPE, [93] as well as the available experimental measurements [94][95][96][97][98][99][100][101][102] and the recommended [81] value of k 7 (T) = 2.7 10 À11 exp(224/T) cm 3 s À1 which is valid over the temperature range 200 T/K 400. The significant result is that k 7 (T) is inhibited by vibrationally exciting HO 2 when compared with the case [93] where HO 2 is initially in the ground vibrational state, although its magnitude still fits within the error bars of the recommended [81] rate constant (except, perhaps, at low temperatures).…”
mentioning
confidence: 84%
“…For example, at T = 255 K, such a decrease is 44 % for DMBE I and 36 % for DMBE II. This may be rationalized from the fact that, for a fixed vibrational excitation [93] of HO 2 , the rate constant increases slightly more in the case of DMBE II than in the case of DMBE I. However, such a discrepancy diminishes when considering the LTD micropopulation for HO 2 , since there is a high fraction of HO * 2 species that reacts via other channels.…”
mentioning
confidence: 99%
“…For example, although it has been noted (AdlerGolden, 1997) that the reaction O + HO 2 could be a potential candidate, previous work (Kaye, 1988) has shown that it is unlikely to play a crucial role in studies of the high atmosphere. Although this assumption is possibly valid for HO 2 in the ground vibrational state as the dynamics only yields OH(v ≤ 6), the argument no longer holds if non-LTE is considered, since up to OH(v = 15) products can then be formed (Silveira et al, 2004;Varandas, 2005b). In addition, the reaction of OH + O 3 has been shown to yield HO 2 vibrationally excited above the classical asymptote for dissociation, and thus can be another potential source of OH(v ) Zhang and Varandas, 2001).…”
Section: Kinetics Mechanism and Input Datamentioning
confidence: 99%
“…When non-LTE conditions hold, the chemistry changes dramatically due to the differences in the internal energy content of the species involved: endothermic reactions become exothermic with rate constants substantially larger, at times orders of magnitude larger (Silveira et al, 2004;Varandas, 2005b). Although several studies have been devoted to the role of vibrationally excited species in reactions, particularly for the HO x cycle, atmospheric chemistry models of the middle-upper atmosphere neglect non-LTE (see, e.g., von Clarmann et al, 2010 and references therein).…”
Section: Introductionmentioning
confidence: 99%